An investigation into revenue generating activities to bridge the funding gap: a case of Zimbabwe Prison and Correctional Service for the period 2011-2013 - Danda, Tichakura (Midlands Sate University, 2015)
This research seeks to provide the ways of increasing revenue at Zimbabwe prison and correctional service to mitigate the funding gap and thereby improving its financial performance. The research’s explored ways or strategies available to enhance finance, alternative ways of enhancing finance and the best practices to implement strategies to enhance finance. The researcher got relevant literature from different authors and formulated research questions and objectives which gave guidance to the researcher when the research was being carried out. Research methodology used was quantitative research method. The descriptive research design was used by the researcher where interviews were carried out and questionnaires distributed to the management and staff of Zimbabwe Prison and Correctional Service. Four interviews that were planned three were conducted successfully and there was an 80% response rate for the questionnaire. Pie charts, bar graphs and tables were used to present the data gathered. The findings from the research are most respondents agreed an the problems affecting service delivery at correctional centres. The respondents also agreed on the strategies that can be used to enhance finance. The researcher recommended that Zimbabwe Prison and correctional service should make imprisonment mainly for violent offenders. Non- violent offenders who are charged with short jail terms are best considered to do community service and this will reduce the prison population and this will in turn increase the availability of funds .Recidivism should also be reduced by developing programs that will reintegrate offenders back into the society thereby reducing the chances of re-offending.